Решить пример полностью и найти промежуток. подробнее : )​

Сменка Сменка    3   13.11.2019 21:20    0

Ответы
kopilge kopilge  05.08.2020 10:22

x= 0∈ [0; 3)

Пошаговое объяснение:

\frac{(3x-4)^{2}}{6} -\frac{(2x-1)(2x+1)}{3}=3+\frac{x^{2} }{6}

\frac{9x^{2} -24x+16}{6} -\frac{4x^{2} -1}{3}-\frac{x^{2} }{6}-3=0

\frac{9x^{2} -24x+16}{6} -\frac{8x^{2} -2}{6}-\frac{x^{2} }{6}-3=0

\frac{9x^{2} -8x^{2} - x^{2} -24x+16+2-18}{6}=0

-24x=0

x= 0

x= 0∈ [0; 3)

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика